2017
DOI: 10.36876/smjhrt.1014
|View full text |Cite
|
Sign up to set email alerts
|

A Retrospective Analysis Comparing Treatment Response for Visceral Leishmaniasis-HIV Co-Infected Patients from the New World

Abstract: Background: Visceral Leishmaniasis and Human Immunodeficiency Virus co-infection (VL-HIV) occurs mainly in risk groups for HIV/AIDS (youth adult males). These co-infected individuals have greater mortality and relapses rates compared to VL as they share similar immune pathogenic mechanisms. Interest in co-infection VL/HIV and the lack of data in the literature led the authors to a survey on the subject comparing outcomes in VL-HIV co-infected treated with different drugs anti-Leishmania used in Brazil, such th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…A previous study, matching ours, reported that age was a positive predictor of response at SVR12 and SVR24. However, given that the odds ratio (1.03) was very small, and that advanced age rarely leads to better clinical outcomes, this was likely statistical noise due to small power rather than a real effect of the predictor [12] .…”
Section: Discussionmentioning
confidence: 99%
“…A previous study, matching ours, reported that age was a positive predictor of response at SVR12 and SVR24. However, given that the odds ratio (1.03) was very small, and that advanced age rarely leads to better clinical outcomes, this was likely statistical noise due to small power rather than a real effect of the predictor [12] .…”
Section: Discussionmentioning
confidence: 99%
“…7 In addition, elevated parasite load is a common finding in coinfected patients, due to the compromised immune system (reduced monocyte and macrophage function) and stimulation of viral replication. 8,9 Serological tests for antibodies normally show low performance for VL/HIV coinfected patients. Freire et al 10 demonstrated that, among serological tests available in Brazil for diagnosing VL, DAT showed the highest sensitivity in individuals with coinfection, and immunochromatographic assay (IT LEISH, rk39) showed sensitivity of only 63.2%.…”
Section: Discussionmentioning
confidence: 99%
“…24,25 In individuals with VL-HIV coinfection, the chance of recurrence of VL is five times greater than in individuals without coinfection. 9 The high rate of recurrence may be associated with the inability to control replication of parasites due to an ineffective immune response mediated by Leishmaniaspecific lymphocytes, resulting from immunodeficiency caused by HIV. 26 In the reported case, the patient showed clinical worsening 6 months after treatment of VL, as he did not follow up with secondary prophylaxis.…”
Section: Discussionmentioning
confidence: 99%